Pemanfaatan Eco-enzyme Sebagai Inovasi Pengendalian Mikrobiologis Udara Dalam Ruang - Zaenab Zaenab; Nurfitriani Azizah (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Air in rooms contaminated by microorganisms such as bacteria can cause health problems, especially respiratory tract infections. The use of eco-enzymes as a natural disinfectant is an environmentally friendly alternative to control airborne bacteria. This study aims to determine the effectiveness of eco-enzyme at concentrations of 15%, 20%, and 25% in reducing airborne bacteria levels in indoor spaces. The research method used a Quasi-Experimental design with a Pre-Post Test Control Group. Samples were collected from three classrooms at SMA Negeri 12 Makassar using random sampling. The eco-enzyme concentrations tested were 15%, 20%, and 25%, with a contact time of 1 hour. Data were analyzed using a One-Way ANOVA test. The results showed a significant reduction in airborne bacteria levels at all concentrations: 15% reduced by 14%, 20% by 24%, and 25% by 76%. Meanwhile, the control group experienced an increase in bacterial counts by 27%. Statistical analysis showed significant differences, with the 25% concentration being the most optimal (p-value 0.0001 < 0.05). Eco-enzyme at a concentration of 25% was proven effective in reducing airborne bacteria and has potential as an environmentally friendly natural disinfectant. This study has limitations, such as the use of a simple application method (manual sprayer) and a limited number of samples, so further research is recommended using the dry mist method and a broader sample scope. Keywords: Eco-enzyme; Natural Disinfectant; Air Bacterial Count; Indoor Air